ALAT ANALISIS KRONOLOGI KONFLIK DALAM PENGGUSURAN LAHAN PEKAYON-JAKASETIA SEBAGAI KONFLIK AGRARIA - Yuliantika, Dewi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
The Pekayon-Jakasetia eviction conflict has been going on since 2016 which occurred due to a feud between the owner or residents affected by the eviction of Pekayon-Jakasetia and the Bekasi City Government, which is carrying out a program of the Ministry of Public Works and Housing which is intended to build pedestrians, parks and roads. This eviction conflict is related to agrarian conflict which is a dispute or conflict with land issues, either in the form of control or land ownership. The Pekayon-Jakasetia eviction conflict has resulted in opposition from the local community for evictions without dialogue and only with a warning letter five times in five weeks without dialogue with the people affected by the evictions, even though the land is free state land and has been inhabited in good faith for decades. In fact, the government also compensates the people affected by the evictions as a form of compensation. Thus, people who feel aggrieved and do not receive protection, as well as responsibility for the forced evictions. This paper aims to map the sequence of events for the evictions using qualitative methods through literature study. Sources of data are obtained from books, journals and internet sites.